The determinants perception towards tax evasion ethics among Putrajaya residents / Durratul Nafisah Abd Rahman - Abd Rahman, Durratul Nafisah (Faculty of Business and Management, 2019)
Tax evasion has become the country issue since years ago including Malaysia. Tax is the important source of government income to cover country's infrastructure and else. However, if people evade taxes there will be major loss to government revenue. This study aimed to examine the determinants perception toward tax evasion ethics from Putrajaya residents. This study is using four variables to determine the determinants factor which is justice, tax system, discrimination and love of money. The data were collected through the distribution of questionnaires to 100 respondents in Putrajaya and processed using Statistical Package for Social Science (SPSS) software for the purpose of this study. By using regression analysis, the findings of the study show that there are positively significant relationship between justice, tax system and discrimination. However, love of money turned out to be negatively significant correlation with tax evasion.